2014
DOI: 10.1038/bjc.2013.802
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2 amplification has prognostic significance in gastric cancer: results from a large international multicentre study

Abstract: Background:In preclinical gastric cancer (GC) models, FGFR2 amplification was associated with increased tumour cell proliferation and survival, and drugs targeting this pathway are now in clinical trials.Methods:FGFR2 FISH was performed on 961 GCs from the United Kingdom, China and Korea, and the relationship with clinicopathological data and overlap with HER2 amplification were analysed.Results:The prevalence of FGFR2 amplification was similar between the three cohorts (UK 7.4%, China 4.6% and Korea 4.2%), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
134
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 44 publications
(72 reference statements)
9
134
1
2
Order By: Relevance
“…13,18 In this large-scale study with 1974 gastric cancer patients, FGFR2 amplification and FGFR2b overexpression were more commonly identified in poorly differentiated tumors with diffuse histology, which is different from other reports. 4,15 Diffuse histology was found in most tumors with high 15 In this study, although FGFR2 amplification itself was not associated with overall survival, FGFR2b overexpression with high H-score showed strong prognostic value for survival.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…13,18 In this large-scale study with 1974 gastric cancer patients, FGFR2 amplification and FGFR2b overexpression were more commonly identified in poorly differentiated tumors with diffuse histology, which is different from other reports. 4,15 Diffuse histology was found in most tumors with high 15 In this study, although FGFR2 amplification itself was not associated with overall survival, FGFR2b overexpression with high H-score showed strong prognostic value for survival.…”
Section: Discussioncontrasting
confidence: 75%
“…4,15 Diffuse histology was found in most tumors with high 15 In this study, although FGFR2 amplification itself was not associated with overall survival, FGFR2b overexpression with high H-score showed strong prognostic value for survival. Considering the controversial clinical significance and high intratumoral heterogeneity of FGFR2 amplification in gastric cancer, 13,18 the extent of FGFR2b overexpression, rather than the presence of FGFR2 amplification itself, may be a better predictor of patient survival. Because FGFR2 FISH assays traditionally only examine a small portion of the tumor, whereas immunohistochemistry assays provide data on the entire tumor section, immunohistochemistry may be a better assay to cover intratumoral heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study it as been reported that FGFR1 is an independent negative prognostic factor in surgically resected SCCL and is associated with cigarette smoking (Kim et al, 2016a;Kim et al, 2016b). In gastric cancer, FGFR2 amplification was detected in 4.2-7.4% of cases and has been correlated with poor prognosis and lymphatic invasion (Su et al, 2014). Recently a study screened 312 gastric cancer patients demonstrating that FGFR2 amplification is correlated with a metastatic status at the diagnosis and a poor prognosis .…”
Section: Fgfr In Cancermentioning
confidence: 97%